The Central Cattle Pattern and interpreting the past - Huffman, T. N. (Southern African Humanities, 2021)
Criticisms of the Central Cattle Pattern raise a number of issues in African archaeology; for example the use of ethnographic analogy, identity versus worldview, the nature and extent of cultural change over time, and hypothesis comparison. While necessary, the criticisms are without substance. At a general level the Central Cattle Pattern provides insights into the antiquity of bridewealth in cattle and the origins of the Zimbabwe culture. As a high-level normative model, however, it is not equipped to explain variation in detail. To cite this article: Huffman, T.N. 2001. The Central Cattle Pattern and interpreting the past. Southern African Humanities 13: 19-35.